New coronavirus: what does nursing have to learn and teach in times of a pandemic? - Marli Terezinha Stein Backes; Karini Manhães de Carvalho; Evangelia Kotzias Atherino dos Santos; Dirce Stein Backes (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To promote a theoretical reflective analysis of what nursing has to learn and teach to global society in times of OVID-19 pandemic. Methods: Reflective theoretical essay aimed at contributing new knowledge and raising new questions, based on the assumptions of Edgar Morin's complexity thinking, subsidized by readings of texts extracted from electronic databases, as well as speeches by health professionals available in open communication tools. Results: COVID-19 reiterates that the biological warfare of the current pandemic is not fought with nuclear or fire weapons, but with care in its multiple dimensions: physical, emotional, spiritual, family, social, political and economic. Final considerations: Nursing has to learn and teach global society that its main object of work, care, is related to the expansion of systemic interactions and associations and the capacity to strengthen the interlocution with complex reality.